1993
DOI: 10.1002/jnr.490360111
|View full text |Cite
|
Sign up to set email alerts
|

Myelin basic protein mRNA translocation in oligodendrocytes is inhibited by astrocytes in vitro

Abstract: Myelin basic protein (MBP) mRNAs are translocated from cell bodies into the slender processes connecting oligodendrocyte somas with the myelin sheath in vivo. This translocation was observed in mixed glial cultures prepared from newborn mouse brains and it occurred in approximately 25% of the cells expressing the gene. However, when "enriched" oligodendrocytes were prepared by shaking them free of other glial cells, MBP mRNA translocation occurred into the processes of essentially all of the cells. When enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 44 publications
1
40
0
Order By: Relevance
“…Enriched oligodendrocytes were prepared as described by Amur-Umarjee et al (1993). First, cerebral hemispheres from 0-to 1-d-old mice were mechanically dissociated and were plated on polylysine-coated flasks in DMEM/Ham's F12 media containing 6 g/L glucose and 10% FBS.…”
Section: Analysis Of the Golli Ko Transgenic Micementioning
confidence: 99%
“…Enriched oligodendrocytes were prepared as described by Amur-Umarjee et al (1993). First, cerebral hemispheres from 0-to 1-d-old mice were mechanically dissociated and were plated on polylysine-coated flasks in DMEM/Ham's F12 media containing 6 g/L glucose and 10% FBS.…”
Section: Analysis Of the Golli Ko Transgenic Micementioning
confidence: 99%
“…Subsequent experiments demonstrated that MBP mRNA is translated close to myelin and the protein rapidly incorporated into the nascent membrane (14 -16) and lead to a model in which MBP mRNA is recruited into RNA transport granules in the perikaryon and then transported, by indirect attachment to the microtubule-bound motor protein kinesin, to the myelin compartment at the cell periphery (10,(17)(18)(19)(20)(21). The granules are localized in the myelin compartment, and the RNA cargo is translated, with the MBP being incorporated into the myelin membrane.…”
mentioning
confidence: 99%
“…Distribution into processes more closely parallels the situation in normal OLs. Since restriction of MBP mRNA to the cell soma has been correlated with physical content between astrocytes and normal OLs, 25 it is interesting that the effect of astrocyte secreted factors has an opposite effect on many jp OLs.…”
Section: Jimpy Oligodendrocyte Survival and Differentiation Can Be Enmentioning
confidence: 99%